THE ROLES OF FORENSIC ACCOUNTANTS IN PREVENTION AND DETECTION OF MONEY LAUNDERING IN PHOENIX ACTIVITIES - Samuel Anindyo Widhoyoko; Deoga Payudha; Jeannada Natasha; Jerremy Immanuel (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2017)
The process of company liquidation is always full of money laundering allegations and vulnerable to fraud. This fraudulent scheme is referred to as phoenix activity. The main purpose of phoenix activity is to avoid liability and expenses, which detriments the stakeholders. This research explains the importance of the role of forensic accountants prior, during, and after bankruptcy. The methodology used in this research is literature review examining the problems through various researches and frameworks. The literature review discusses three aspects related to fraudulent bankruptcy scheme i.e. motivation, the scheme processes and litigation processes. The research concludes that the presence of forensic accountants is important in the insolvency prevention and detection, in their roles as(1) independent and hired experts; (2) professional legal assistance providers of Anti-Money Laundering (AML) and asset manager; (3) business valuation experts; (4) private investigators; and (5) surveillance body for anti-money laundering purposes.